Using an Audiovisual Materials-Based Teaching Strategy to Improve EFL Young Learners' Understanding of Instructions - Gemalli Ulloa Salazar; Claudio Díaz Larenas (Asociación Colombiana de Profesores de Ingles, 2018)
Conducted in a semi-public school in Chile, this action research study aims at determining the change in 18 English as a foreign language young learners' performance regarding their understanding of instructions after being exposed to an audiovisual materials-based teaching strategy. With the use of a lesson observation report for assessing the way they follow instructions and a Likert scale to analyze their attitudes towards the strategy, findings show there was a positive change in their performances and that these learners regard this strategy as beneficial, which supports the belief that the inclusion of audiovisual aids benefits young learners when learning English.